The Impact of Facility Quality and Teacher Competence on Religious Practice Skills in Kindergarten Education - Joni; Alim, Melvi Lesmana; Hadi, Cipto; Nurmalina (Universitas PGRI Yogyakarta, 2025)
The ability of young children to practice religion is one of the main objectives of kindergarten education, which is influenced by various internal and external factors of the school. However, research examining the simultaneous contribution of facility quality and teacher competence in supporting religious practice abilities is still limited. This study aims to analyze the influence of facility quality and teacher competence on religious practice abilities at RA Arrahman Pekanbaru. A quantitative method, involving a correlational survey, was employed, utilizing a 50-item Likert scale questionnaire and 60 respondents (parents). Regression analysis revealed that both variables were significantly influential, with an R² of 0.682; facility quality (β = 0.451) contributed more to the model than teacher competence (β = 0.392). These findings highlight the importance of integrating both tangible (facility quality) and intangible (teacher competence) factors in supporting the success of religious practice among kindergarten children. The uniqueness of this study lies in the empirical evidence of the dominance of facilities in the Indonesian context. Practical implications suggest that educational institution managers should balance investments in infrastructure and teacher capacity development to strengthen the implementation of religious values from an early age. Keywords: quality of facilities, teacher competence, religious practice ability, early childhood education, service quality